2020
DOI: 10.1111/jan.14572
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ psychological changes and coping strategies during home isolation for the 2019 novel coronavirus in China: A qualitative study

Abstract: Aims To explore the psychological changes of nurses during home isolation, the factors that related with these changes, and coping strategies in home isolation during the epidemic of COVID‐19 in China. Design A qualitative study based on grounded theory. Methods Individual semi‐structured telephone interviews were conducted from January 2020‐February 2020 with 10 nurses who were isolated at home sharing the experiences of the epidemic of COVID‐19. All interviews were audio recorded, transcribed, and analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 29 publications
(33 reference statements)
0
39
0
4
Order By: Relevance
“…In the 13 research studies included in the scoping review ( Table 3 ), 3,613 nurses expressed their thoughts and praised coping techniques. The papers included 7 cross-sectional studies [ [52] , [53] , [54] , [55] , [56] , 58 , 61 ], 2 qualitative study [ 57 , 59 ], 2 mixed-method studies [ 60 , 62 ], 1 comparative study [ 64 ], and 1 pilot-based study [ 63 ]. Of these, 4 studies are from China [ 53 , [57] , [58] , [59] , 64 ], and 3 from America [ 55 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 13 research studies included in the scoping review ( Table 3 ), 3,613 nurses expressed their thoughts and praised coping techniques. The papers included 7 cross-sectional studies [ [52] , [53] , [54] , [55] , [56] , 58 , 61 ], 2 qualitative study [ 57 , 59 ], 2 mixed-method studies [ 60 , 62 ], 1 comparative study [ 64 ], and 1 pilot-based study [ 63 ]. Of these, 4 studies are from China [ 53 , [57] , [58] , [59] , 64 ], and 3 from America [ 55 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The papers included 7 cross-sectional studies [ [52] , [53] , [54] , [55] , [56] , 58 , 61 ], 2 qualitative study [ 57 , 59 ], 2 mixed-method studies [ 60 , 62 ], 1 comparative study [ 64 ], and 1 pilot-based study [ 63 ]. Of these, 4 studies are from China [ 53 , [57] , [58] , [59] , 64 ], and 3 from America [ 55 , 60 , 61 ]. The research covered both males and females.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, anger, fear, sadness, disgust, and uncertainty were emotions reported by Spanish citizens during their lockdown at the first COVID-19 outbreak [ 34 ]. Zhang et al [ 35 ] also reported that health professionals (nurses) had several negative emotional reactions in the early stages of home isolation. Therefore, it seems that healthcare professionals, independent of the profession, experienced a double stress situation, professional overload and personal/familiar lockdown, during the first COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when working during the COVID‐19 pandemic, healthcare providers find it difficult to work with heavy protective equipment, as it makes it difficult for them to move their body and conduct various procedures, which is the same as professional nurses who experience difficulties in performing their tasks during the COVID‐19 pandemic as well (Galehdar et al., 2020 ; Thobaity & Alshammari, 2020 ). However, even though the pandemic causes stressfulness and difficulty, it makes the novice nurses feel proud of being on the frontline taking care of COVID‐19 patients and being part of the team that is tasked with caring for patients during the COVID‐19 pandemic, equal to nurses and healthcare providers who provide care for COVID‐19 patients all across the world (Hu et al., 2020 ; LoGuidice & Bartos, 2021 ; Zhang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%